Cloud-oriented learning environment of secondary school - Svitlana H. Lytvynova (CTE Workshop Proceedings, 2018)
Research goals: to outline the state of secondary education to implement a cloud-oriented learning environment (COLE), establishing research objectives: to determine the readiness of students to the introduction of COLE, to develop a conceptual framework of cooperation in COLE at the level of the institution, identify the actors interact COLE. The object of research supports the learning environment secondary schools; subject – a cloud-oriented learning environment of secondary schools. Research methods used: analysis of statistics and publications. Experimental research and conducted in secondary schools Obolon district of Kyiv. Intermediate results: the architecture of COLE 44 secondary schools of the district, introduced more than 10 thousand accounts established electronic interaction between teachers and students by e-mail Outlook. Currently under development cloud storage (SkyDrive) training materials teachers practiced the skills of teamwork and planning tools calendars. The main conclusions and recommendations. Implementation of COLE at secondary schools provides endless opportunities both teacher and student, in fact created conditions for innovation and learning. Without a doubt we can say that for the future of Honshu, for full use must have a quality Internet, motivated teachers. For subjects of the educational process, the conditions of access to learning materials anywhere, anytime, and it activates the cognitive and creative activity of students that will improve key indicators of learning.